Pengaruh Kadar Serbuk Gergaji Dalam Proses Bioremediasi Tanah Tercemar Minyak - Putri, Ade Rahayu; Amraini, Said Zul; Bahruddin, Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Bioremediation is one of the most cost-effective and environmentally friendly methods to remediate many different types of waste materials widely used by many private and public entities. This research was conducted to determine the influence rates of sawdust in the bioremediation process of petroleum contaminated soil by using laboratory methods, in combination with the addition of fertilizer as sources of nitrogen. This research was conducted based on the 100:5:1 of C:N:P ratios, respectively. Test parameters needed to knowing the optimal condition in remediation were pH, moisture content and temperature. Results show the Total Petroleum Hydrocarbon (TPH) was degraded until 44% for the addition of 500 grams sawdust size 0.2 cm, 33% for the addition of 750 grams sawdust size 3 cm and 20% without any treatment within around two months. The addition of sawdust and fertilizer has increased the efficiency of TPH degradation and obtained positive relationship for the addition of fertilizer to the level of TPH degradation.  Keywords: bioremediation, sawdust, degradation, TPH, fertilizer